Treatment of comminuted intra-articular fractures of the distal radius by open reduction and volar plating in adults [Yetişkinlerde parçali intraartiküler distal radius kiriklarinin açik redüksiyon ve voler plaklamayla tedavisi] - (:unkn) unknown (My University, 2006)
BACKGROUND: We herein present the mid-term results of the adult patients with communited intra-articular fractures of the distal radius who were treated by palmar plating. METHODS: Between 1999 and 2003, open reduction and palmar plating were performed in 23 of the patients who had surgical treatment for comminuted intra-articular fractures of the distal radius. Nineteen patients (11 females, 8 males; mean age 34; range 22 to 54 years) with regular follow-up were included in the study. In the majority of patients only one wrist was involved (7 dominant - 12 nondominant). Preoperative evaluation included patient's history, physical examination, and radiological studies (plain radiographs, computed tomography). The patients were classified according to AO classification as 7 type B [B1 (1); B2 (3); B3 (3)] and 12 type C [C1 (7); C2 (5)]. The surgical procedure included internal fixation by using plates and screws with palmar approach. Range of motion exercises were started immediately after the operations. The patients were followed clinically and radiographically, with an average follow-up time of 28 months (range, 13-47 months). Complications were recorded. RESULTS: Union was achieved in all patients. Radiographic parameters including the radial height, radial inclination, palmar tilt, and articular congruency have been corrected in the operation and remained unchanged until the last follow-up. According to the Gartland and Wer ley's classification, there were 9 (47%) excellent, 7 (37%) good, and 3 (16%) fair results. No perioperative and postoperative complications were recorded, except for three wound problems and one prolonged scar tenderness. CONCLUSION: Palmar plating is a safe and effective treatment for comminuted intraarticular fractures of the distal radius, regardless of direction of displacement of the distal fragment.
Keywords: Distal radius fracture; Internal fixation; Palmar plating